2019
DOI: 10.3390/metabo10010001
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Analysis of the Mouse Gut Microbiome Response to the Persistent Organic Pollutant 2,3,7,8-Tetrachlorodibenzofuran

Abstract: Persistent organic pollutants (POPs) are important environmental chemicals and continued study of their mechanism of action remains a high priority.POPs, such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), 2,3,7,8-tetrachlorodibenzofuran (TCDF), and polychlorinated biphenyls (PCBs), are widespread environmental contaminants that are agonists for the aryl hydrocarbon receptor (AHR). Activation of the AHR modulates the gut microbiome community structure and function, host immunity, and the host metabolome. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
2
15
1
Order By: Relevance
“…We identified general transcriptional responses to most POPs related to energy metabolism pathways including the TCA cycle, butyrate metabolism, and pyruvate metabolism, supported by our metabolomics data. Similar observations have been reported in a previous mouse study 20 and an in vitro study that reported a dose-dependent inhibitory effect and a disruption in bacterial fermentation processes by PCB 126 exposure using a mouse fecal culture. 36 The direct in vitro effects may translate into microbiome shifts in vivo, which contribute to the disruption of glucose tolerance in host with POPs exposure.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We identified general transcriptional responses to most POPs related to energy metabolism pathways including the TCA cycle, butyrate metabolism, and pyruvate metabolism, supported by our metabolomics data. Similar observations have been reported in a previous mouse study 20 and an in vitro study that reported a dose-dependent inhibitory effect and a disruption in bacterial fermentation processes by PCB 126 exposure using a mouse fecal culture. 36 The direct in vitro effects may translate into microbiome shifts in vivo, which contribute to the disruption of glucose tolerance in host with POPs exposure.…”
Section: Discussionsupporting
confidence: 91%
“…Another prominent finding in this study was the integrated and detailed characterization of the altered metabolic pathways using metatranscriptomics data combined with metabolomics data. Oral POP treatment modulated the microbial community, 13,20 which was not fully consistent with what we observed in the in vitro study. The differences could be due to intervention duration and/or the lack of host-mediated processes in in vitro systems.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations